SWOT ANALYSIS OF TOURISM POTENTIAL IN THE SOUTHERN CENTRAL REGION - Nguyễn Thị Thanh Ngân (Tạp chí Khoa học Đại học Đà Lạt)
The Southern Central region has notable tourism potential. Tourism potential is the basic condition for tourism development. This paper uses techniques for SWOT analysis to identify strengths, weaknesses of tourism potential in the Southern Central region and opportunities and challenges to cope with. The specific elements of the tourism potential of the region have been identified, and the results of the study are recommended for further studies.